Research progress of SOCS in autoimmune diseases: mechanisms and therapeutic implications - Cui, Rongqi; Zhang, Jing (Frontiers in Immunology, 2025)
Suppressor of cytokine signaling (SOCS) is a family of regulatory factors whose expression can be induced by various cytokines, growth factors, and hormones. Autoimmune diseases, chronic inflammatory conditions caused by abnormal immune responses, involve overactive T-cells and B-cells, excessive autoantibody production, and damage to multiple organs and systems. The pathogenic mechanisms of autoimmune diseases are complex, and SOCS proteins, particularly SOCS1, SOCS2, SOCS3, and SOCS5, regulate cytokine receptor signaling through distinct mechanisms, thereby participating in the development and progression of autoimmune diseases. This positions SOCS proteins as potential therapeutic targets for modulating dysregulated immune responses in autoimmune diseases.